2013
DOI: 10.1007/s12010-013-0531-5
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Indigenous Plant Seed Oil for the Production of Bio-fuel by an Oleaginous Fungus, Cunninghamella blakesleeana- JSK2, Isolated from Tropical Soil

Abstract: Cunninghamella blakesleeana-JSK2, a gamma-linolenic acid (GLA) producing tropical fungal isolate, was utilized as a tool to evaluate the influence of various plant seed oils on biomass, oleagenicity and bio-fuel production. The fungus accumulated 26 % total lipid of their dry biomass (2 g/l) and 13 % of GLA in its total fatty acid. Among the various plant seed oils tested as carbon sources for biotransformation studies, watermelon oil had an effect on biomass and total lipid increasing up to 9.24 g/l and 34 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…Our study showed that several Mucoromycota fungi have relatively low biomass production under lipogenesis conditions. Thus, the results of low biomass for Rhizopus (oryzae) and CBL were in accordance with the previously performed study by Janakiraman ( 2014 ). Furthermore, the biomass and lipid production of RST were quite low, approx.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that several Mucoromycota fungi have relatively low biomass production under lipogenesis conditions. Thus, the results of low biomass for Rhizopus (oryzae) and CBL were in accordance with the previously performed study by Janakiraman ( 2014 ). Furthermore, the biomass and lipid production of RST were quite low, approx.…”
Section: Discussionsupporting
confidence: 92%